2012
DOI: 10.1111/j.1467-9663.2012.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Reading Time‐Geography from a Gender Perspective: Examples from Gendered mobility

Abstract: This paper is based on qualitative research on commuting and women's everyday lives. In the project 'Re-reading time-geography from a feminist perspective', labour force mobility is an important way of analysing women's time-space use and identifying the constraints experienced when organising everyday life. We claim that time-geography provides a useful set of analytical tools that successfully collaborate with social science theory such as gender studies. Timegeography has been questioned by feminists as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 22 publications
0
25
0
3
Order By: Relevance
“…Nevertheless, it has been pointed out that while women present less overall travel times and less commuting times, other mediating factors play an important role for them, such as the amount of working hours (McQuaid & Chen ; Scholten et al . ). A range of studies have found that age is also a significant factor in determining daily travel time (Schwanen et al .…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, it has been pointed out that while women present less overall travel times and less commuting times, other mediating factors play an important role for them, such as the amount of working hours (McQuaid & Chen ; Scholten et al . ). A range of studies have found that age is also a significant factor in determining daily travel time (Schwanen et al .…”
Section: Introductionmentioning
confidence: 97%
“…In line with feminist critiques of time-geography, however, it is crucial to recognize the significance of corporeality in relation to time and space. 88 While the control of mobility and the confinement of intersectional bodies to the private sphere-away from the so-called illicit activities of the night-is seen as essential to maintain respectability, the embodied acts of dancing and mingling with men in broad daylight act as resistance to this control. The embodied placemaking performed through the transformation of…”
Section: The Nighttime Spacementioning
confidence: 99%
“…From a gender perspective, Scholten et al (2012) highlight how long-distance commuting women experience their everyday mobility and the balance between family and work. The authors caught the embodied experiences of travel, how time and space limit the women's choice of modes of transport but also release time to read, prepare, rest and readjust between different roles as mother, wife and professional.…”
Section: Meanings and Experiences Of Travelling In Time And Spacementioning
confidence: 99%